Acute onset of hip pain and swelling with calcification mimicking pyogenic myositis - Kazuhiro Ishikawa (Clinical Case Reports, 2023)
Abstract In cases with acute hip pain, noninflammatory orthopedics diseases are common. But we sometimes experience acute pyomyositis with high inflammation. Although a rare case, we consider calcific tendonitis and pyogenic myositis.